Determinants of profitability in Chinese commercial banking sector - LIU, XUEGE (2018)
This paper investigates the determinants of bank profitability in China during the periods of 2011 to 2016, using a balanced panel data of 45 commercial banks and system generalized method of moment model to obtain the final results. Our paper using ROAE as dependent variable and considering the bank-specific indicators and macroeconomic variables. And according to the final results of our study, we can discover the key factors which exert significant effects on profitability and analyze the reasons.